The charge transport mechanisms in conducting polymer polypyrrole films and fibers. (24th August 2018) - Ghanbari, Reza; Ghorbani, Shaban Reza; Arabi, Hadi; Foroughi, Javad
Abstract: Smart materials based on inherently conducting polymers are of practical interest and extend the advantages of electromaterials from the nanoscale to macroscale applications. However understanding mechanisms of the their electrical properties are still remained challanging. Herein, we report the transport properties of chemically and electrochemically preapred conducting polymer polypyrrole films and fibers. Conduction mechanisms of the as-prepared polypyrrole (PPy) were investigated using their electrical properties as a function of temperature (7–300 K). The results of the PPy resistivity were evaluated using a linear combination of Mott's and Efros-Shklovskii's Variable-Range Hopping (Mott-VRH and ES-VRH) models. It was found that the localization length was about 10 and 15 monomer units for the PPy-fiber and PPy-film, respectively. The contributions of Mott-and ES-VRH conductivities versus temperature exhibited that electrical conductivity of the PPy-film is two-dimensional Mott-VRH at temperatures of lower than ∼100 K. It was indicated that the contribution of ES-VRH are larger than the contribution of Mott-VRH at temperatures of higher than ∼185 K. It was also found that ES-VRH law predominates at room temperature showed that average size of crystallites in the PPy-film was about three times larger than PPy-fiber.